Chemical Modifications of Alginates for Biomedical Applications-A Review - Qureshi, Muhammad Naqeeb Ur Rehman; Rasool, Atta; Qureshi, Muhammad Anees Ur Rehman; Javaid, Muhammad Jahanzaib; Kanwal, Maria; Anwar, Muhammad Asad; Butt, Muhammad Shoaib; Firdous, Naila (Scientific Inquiry and Review, 2025)
In current pharmaceutical developments, biopolymers have earned a unique position as a choice of excipient not only by affecting formulation developments but also by imparting biocompatibility, degradability, and stimuli responsiveness for controlled drug release in living systems. Alginate (Alg) is a versatile, flexible, bioactive, non-toxic, and inexpensive biopolymer. This is obtained from brown seaweeds and some exo-polysaccharide (EPS) producing-bacteria. Native Alg is susceptible to faster degradation, dimensional instability, de-polymerization at high temperature, and low pH precipitation. Therefore, its chemical modifications attracted researchers to improve biological, chemical, and physicochemical properties in order to improve gelation, strength and cell adhesion for biomedical utilization. This process was carried out by tailoring its hydroxyl and carboxylic functional groups by oxidation, reductive amination, acetylation, phosphorylation, sulfation, esterification, amination, and Ugi reactions. These modifications were achieved by blending, cross-linking, solvent casting, complexation, and grafting. The purpose was to use Alg for improvement in cell affinity, gelation, mechanical trength, structural, functional flexibility, and encapsulation for drug delivery, wound healing, tissue engineering, cancer treatments, bone regenerations, food packaging, metal adsorption, wastewater treatment, and cosmetics. The active sites in the Alg are generated by the use of initiator, cross-linker or irradiation. In this study, sources, properties, and different chemical reactions used to make Alg derivatives are summarized. In conclusion, applications of modified Alg in medico-biological, environmental, and food industry are briefly stated